2020
DOI: 10.5433/1679-0359.2020v41n4p1189
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming dormancy in Bauhinia scandens seeds

Abstract: Bauhinia scandens, an ornamental climbing vine, recently introduced in Brazil, in 2006 which has been gaining prominence due to its anti-tumor medicinal properties. A common feature amongst species of the Fabaceae family is dormancy due to the impermeability of the integument of the seed to water. The demand for seedlings of this species makes it necessary to elucidate the germination process and initial seedling growth. The objective of this study was to determine a method to overcome dormancy, thereby promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In order for the seeds to overcome dormancy and germinate, seeds were immersed in 40 mL of 36 N 95% sulfuric acid for 60 min, rinsed continuously with water through a sieve for 10 min until the acid residues were removed, and dried in the shade (25 °C and 50% RH) on paper towels for 24 h (Jeromini, Pereira, Silva, & Martins, 2020).…”
Section: Germination and Seedling Morphologymentioning
confidence: 99%
“…In order for the seeds to overcome dormancy and germinate, seeds were immersed in 40 mL of 36 N 95% sulfuric acid for 60 min, rinsed continuously with water through a sieve for 10 min until the acid residues were removed, and dried in the shade (25 °C and 50% RH) on paper towels for 24 h (Jeromini, Pereira, Silva, & Martins, 2020).…”
Section: Germination and Seedling Morphologymentioning
confidence: 99%
“…In summary, Bauhinia scandens is liana with ornamental value; the stem forms into a 'monkey ladder' when older; the fruits are pea shaped with 1 to 2 seeds. Apart from Jeromini et al (2020) who studied optimal growing medium for growing Bauhinia scandens seedlings and Jeromini et al (2021) who reported the methods to overcome seed dormancy, very limited studies have been conducted on propagation and culture of this species.According to previous phytochemical screening, the ethanolic extract of its leaves contained some phytochemicals such as phenols, flavonoids, saponins, tannins, alkaloids and steroids which are widely known to have strong relation with medicinal anti-oxidant properties (Lianah et al, 2021). In addition, according to preliminary cytotoxic activity evaluation against HeLa and T47D cell lines, the ethanolic extract of the Bauhinia scandens leaves had potential to be anti-cancer agent (Lianah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%